2014
DOI: 10.1002/ejoc.201403351
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Mediated Deoxygenation of Alcohols with a Dimeric Gold Catalyst

Abstract: A new protocol for the reductive deoxygenation of primary alcohols was explored. This photomediated method combines a novel approach to bromination of alcohols merged with the powerful reducing capability of [Au 2 (dppm) 2 ]Cl 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…79 It has been reported that binuclear gold complexes can also perform photoredox catalysis; this strategy has been applied in radical additions to π systems 80 functional group inter-conversions 81 and other radical coupling reactions. 82 …”
Section: Dual Catalysis With Goldmentioning
confidence: 99%
“…79 It has been reported that binuclear gold complexes can also perform photoredox catalysis; this strategy has been applied in radical additions to π systems 80 functional group inter-conversions 81 and other radical coupling reactions. 82 …”
Section: Dual Catalysis With Goldmentioning
confidence: 99%
“…The mechanism of these reactions via a photoredox dehalogenation–protonation process is established 18,19. Our Stern–Volmer experiments demonstrated the occurrence of the same catalytic cycle in which the transformation was triggered by reductive quenching of the photoredox catalyst (see the ESI†).…”
Section: Resultsmentioning
confidence: 56%
“…Alkyl halides (X) are an important class of readily accessible starting substrates in organic synthesis 16. Since Tanaka and co-workers introduced the visible light-driven reductive dehalogenation of benzyl bromide to benzene in 1984,17 the groups of Kellogg,18 a Fukuzumi,18 b Stephenson,18c–e Zeitler,18 f and Hisaeda18 g and so on18h–o have accomplished the transformation of diverse alkyl halides to alkanes via photoredox catalysis with tertiary amines as the reductant. This conceptual strategy was developed by the Reiser group19 by establishing an alternative reductive system, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In another report, the described method was coupled with a photomediated bromination strategy of alcohols (22)(23)(24)(25)(26) using CBr 4 , leading to an efficient 2-step, one-pot, photomediated deoxygenation protocol (Scheme 4, d). 14 Substrates bearing amino acids, 5-exo-trig and dig amenable moieties, functionalized arenes and sugars were well tolerated, giving products 7, 10, and 30-32 in 70-85% yield.…”
Section: Account Syn Lettmentioning
confidence: 98%